Remote Indigenous Community Empowerment Policy in Realizing Public Service in Darlale Village, Buru Regency - Marno Wance; Rifdan Rifdan; Muhammad Takdir; Arif Ferdian (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: The Remote Indigenous Community or KAT (Komunitas Adat Terpencil) is program carried out in Darlale village by the Buru Regency Social Service, Maluku Province. Based on the results of initial research, people of Darlale village have uninhabitable houses and inadequate levels of education and health. The distance from Namlea city to Darlale village is 173 Km, located in the mountainous region of Buru island. This type of research is a qualitative descriptive analysis and uses the VOS Viewer application to carry out meta-analysis of previous research data. The findings of the field are: (1). The KAT community needs services for building livable houses and are willing to move to a new location (exsite) (2). The community needs adequate educational services. (3). Provision of an adequate road from Darlale village to Wapsait village as main village because the education and health facilities and infrastructure are located in the main village. The implication of the results of the Preliminary Assessment (PA) research is that the Buru Regency Government and the Ministry of Social Affairs will build livable houses and provide health and education facilities.Keywords: KAT Program; Remote Indigenous Community; Livable Houses; Education Level